Lim x- больше (-5) (2x^2+15x+25)/(5-4x-x^2)

Lim x->(-5) (2x^2+15x+25)/(5-4x-x^2)
Гость
Ответ(ы) на вопрос:
Гость
limx->-5 (2x^2+15x+25)/(5-4x-x^2) Разложим числитель и знаменатель на множители: 2x^2+15x+25=0 D=225-200=25 [x=(-15+5)/4=-10/4=-2.5 [x=(-15-5)/4=-20/4=-5 2x^2+15x+25=2(x+2.5)(x+5) 5-4x-x^2=0 x^2+4x-5=0 [x=1 [x=-5 5-4x-x^2=-(x-1)(x+5)  limx->-5 (2x^2+15x+25)/(5-4x-x^2) = limx->-5 (2(x+2.5)(x+5)/-(x-1)(x+5)) = limx->-5 (2(x+2.5)/(1-x)) = 2(-5+2.5)/(1+5) = 2*(-2.5)/6 = -5/6 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы